Limitations of trust management schemes in VANET and countermeasures - Huang, Zhen; Ruj, Sushmita; Cavenaghi, Marcos [UNESP]; Nayak, Amiya (My University, 2011)
Vehicular networks ensure that the information received from any vehicle is promptly and correctly propagated to nearby vehicles, to prevent accidents. A crucial point is how to trust the information transmitted, when the neighboring vehicles are rapidly changing and moving in and out of range. Current trust management schemes for vehicular networks establish trust by voting on the decision received by several nodes, which might not be required for practical scenarios. It might just be enough to check the validity of incoming information. Due to the ephemeral nature of vehicular networks, reputation schemes for mobile ad hoc networks (MANETs) cannot be applied to vehicular ad hoc networks (VANET). We point out several limitations of trust management schemes for VANET. In particular, we identify the problem of information cascading and oversampling, which commonly arise in social networks. Oversampling is a situation in which a node observing two or more nodes, takes into consideration both their opinions equally without knowing that they might have influenced each other in decision making. We show that simple voting for decision making, leads to oversampling and gives incorrect results. We propose an algorithm to overcome this problem in VANET. This is the first paper which discusses the concept of cascading effect and oversampling effects to ad hoc networks. © 2011 IEEE.
Keywords: Information cascading; Information oversampling; Reputation Systems; Security; Vehicular Networks; Over sampling; Reputation systems; Vehicular networks; Accidents; Ad hoc networks; Decision making; Mobile telecommunication systems; Network management; Vehicular ad hoc networks